Pengalaman Program Praktik Mengajar, Kreativitas, dan Locus of Control untuk Siapan Menjadi Guru Era Revolusi Industri 4.0 - Rosmiati Rosmiati; Zuhri Saputra Hutabarat (IKIP PGRI Bojonegoro, 2022)
Abstract: The purpose of this study was to determine the readiness of students to become teachers in the era of the industrial revolution 4.0. Educational progress is closely related to the industrial revolution 4.0 which is used to support the learning process wherever it is located. Through the experience of teaching practice programs, the way prospective teachers are able to develop their educational knowledge competencies in the COVID-19 situation is by increasing creativity through the use of various technological advances along with the times. So as to create the next generation of the nation that is superior, able to compete, and ready to become competent and professional teachers of the industrial revolution 4.0 era. This study uses a quantitative approach using survey methods. In managing the results of this study, the Slovin formula is used to represent the entire population of 755 using a Likert scale to measure each of the indicators of the variables studied, about a series of statements given in the form of a questionnaire and distributed online via google form. The research sample was 261 prospective teacher respondents who had finished implementing the teaching practice program in schools in Jambi Province, then after the data had been collected they were analyzed using SEM-PLS. The results of this study are: 1) The formation of the skills of prospective teachers in teaching and guiding students in real in schools by constantly improving and developing the competencies of the educational sciences that he has in accordance with the needs of students in the era of the industrial revolution 4.0, 2) Through experience teaching practice programs in schools, prospective teachers get more learning media references through incorporating learning methods and models according to the needs of students in the era of the industrial revolution 4.0. 3) The role of campuses and schools is to be able to realize intelligent education through improving the quality of education, equitable distribution of education, and expanding access through relevance in realizing prospective economic teachers in the era of the industrial revolution 4.0. Abstrak: Tujuan penelitian ini untuk mengetahui kesiapan mahasiswa menjadi guru era revolusi industri 4.0. Kemajuan pendidikan sangat erat kaitannya dengan revolusi industri 4.0 yang dimanfaatkan untuk mendukung proses pembelajaran di manapun berada. Melalui pengalaman program praktik mengajar, cara calon guru mampu mengembangkan kompetensi ilmu pendidikannya disituasi covid 19, dengan cara meningkatkan kreativitas melalui pemanfaatan berbagai kemajuan teknologi seiring perkembangan zaman. Sehingga tercipta generasi penerus bangsa yang unggul, mampu bersaing, dan siap menjadi guru era revolusi industri 4.0 berkompetensi dan profesional. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan metode survei. Dalam mengelola hasil penelitian ini menggunakan rumus Slovin untuk merepresentasikan seluruh populasi sebanyak 755 dengan menggunakan skala likert untuk mengukur setiap indikator-indikator variabel yang diteliti, tentang serangkaian pernyataan-pernyataan yang diberikan dalam bentuk kuesioner dan disebarkan secara online melalui google form. Sampel penelitian sebanyak 261 responden calon guru yang telah selesai melaksanakan program praktik mengajar di sekolah yang ada Provinsi Jambi, selanjutnya setelah data terkumpul dianalisis dengan menggunakan SEM-PLS. Hasil penelitian ini adalah: 1) Terbentuknya keterampilan calon guru dalam mengajar dan membimbing siswa secara rill di sekolah dengan senantiasa calon guru selalu meningkatkan dan mengembangkan kompetensi-kompetensi ilmu pendidikan yang dia miliki sesuai dengan kebutuhkan siswa di era revolusi industri 4.0, 2) Melalui pengalaman program praktik mengajar di sekolah, calon guru memperoleh lebih banyak referensi media pembelajaran melalui penggabungan metode dan model pembelajaran sesuai kebutuhkan siswa di era revolusi industri 4.0. 3) Peranan kampus dan sekolah mampu mewujudkan pendidikan cerdas melalui peningkatan kualitas pendidikan, pemerataan pendidikan, dan perluasan akses melalui relevansi dalam mewujudkan calon guru ekonomi era revolusi industri 4.0.